A Class of Singularly Perturbed Semilinear Elliptic Equations (Journal of Partial Differential Equations, 2002)
" The singularly perturbed problem for the semilinear elliptic equations is considered. Under appropriate conditions, by using the comparison theorem, the existence and asymptotic behavior of solution for the boundary value problems are studied."